Optimized fertilization patterns increase foxtail millet biomass on the distribution and transformation in Loess Plateau of China. - Tianyou Zhou; Qinhui Liu; Shuangshuang Yang; Zhihao Wang; Panpan Zhang; Xiaolin Wang; Xiaoling Ji; Xiong Zhang (PLoS ONE)
Organic manure or microbial fertilizers are essential sources of plant nutrients to supplement farmland soil, and organic and inorganic fertilizers are considered an effective way to achieve sustainable agriculture by improving the soil and increasing crop yields. This experimental material was used foxtail millet (Setaria italica) "Changsheng 07"and started in the growing season of 2017-2018 in a dry farming area of northern Shaanxi Province, with five different fertilizing patterns, and each four repetitions, including T1(N,45kg·hm-2),T2(N,60kg·hm-2; P2O5 30kg·hm-2),T3(N,90kg·hm-2;P2O5 45kg·hm-2),T4(N,60kg·hm-2;P2O5 40kg·hm-2,Organic matter 2000kg·hm-2),T5(N,60kg·hm-2;P2O5 40kg·hm-2; microbial fertilizer 5kg·hm-2). The results showed that: (1) the above-ground dry matter accumulation with T4 and T5 increased by 15.04% and 33.68% during the flowering and pustulation stages, and the root/shoot ratio of T4 increased by 9.32% and 12.46% over two experimental years, respectively. (2) the leaf water use efficiency (WUEL) of T4 increased by 15.61%, 0.51% in two stages, respectively, (3) the yields and water use efficiency (WUE) of T3 exhibited a significantly increased by 11.06% and 37.61%, 9.50% and 37.51%, and increased stably by 9.23%-35.17% and 8.73%-35.11% in T4 and T5 respectively, over two seasons. In summary, applying organic and inorganic manure could effectively regulate the accumulation and distribution of above-ground biomass of foxtail millet, and ensure the high and stable grain yield.